2023
DOI: 10.1002/hbm.26496
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in endogenous testosterone have sexually‐dimorphic effects on spontaneous cortical dynamics

Giorgia Picci,
Lauren R. Ott,
Samantha H. Penhale
et al.

Abstract: The transition from childhood to adolescence is associated with an influx of sex hormones, which not only facilitates physical and behavioral changes, but also dramatic changes in neural circuitry. While previous work has shown that pubertal hormones modulate structural and functional brain development, few of these studies have focused on the impact that such hormones have on spontaneous cortical activity, and whether these effects are modulated by sex during this critical developmental window. Herein, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 99 publications
(151 reference statements)
0
0
0
Order By: Relevance
“…Other studies have found testosterone to mediate the relationship between age and the beta oscillations serving motor control (Killanin et al, 2023 ) and sensorimotor processing more broadly (Fung et al, 2022 ) in the primary motor cortices. Furthermore, in developing youth, testosterone's relationship with spontaneous cortical activity has been found to differ by sex, with the strongest differences in frontal cortices (Picci, Ott, et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found testosterone to mediate the relationship between age and the beta oscillations serving motor control (Killanin et al, 2023 ) and sensorimotor processing more broadly (Fung et al, 2022 ) in the primary motor cortices. Furthermore, in developing youth, testosterone's relationship with spontaneous cortical activity has been found to differ by sex, with the strongest differences in frontal cortices (Picci, Ott, et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%